(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Development and validation of two simple, accurate, precise and economical UV Spectrophotometric methods for simultaneous estimation of Thiocolchicoside and Dexketoprofen in bulk and in tablet dosage form. The methods employed were Method-1 Absorbance correction method and Method-2 First order derivative spectroscopic method. In method-1 Absorbance is measured at two wavelengths 370nm at which Dexketoprofen has no absorbance and 255nm at which both the drug have considerable absorbance. In method-2, two wavelengths 232nm for Thiocolchicoside (zero cross for Dexketoprofen) and 242nm for Dexketoprofen (zero cross for Thiocolchicoside) were selected. The beers law obeyed in the concentration range 4-40µg/ml and 5-50µg/ml for Thiocolchicoside and Dexketoprofen respectively in methanol. The suggested method is validated by using ICH validation parameters like accuracy, precision, linearity, LOD and LOQ respectively. Recovery study values of Thiocolchicoside and Dexketoprofen was found 99.8% and 100.2% respectively for both the methods. Standard deviation and RSD for intra-day and inter-day precision studies was found to be less than ± 2. The linearity coefficient was found 0.9996 at 242nm and 0.999 at 255 nm for Dexketoprofen and 0.9997 at both 232nm and 370nm for Thiocolchicoside. The LOD and LOQ for Method-1 were found to be 0.0067μg/ml and 0.020μg/ml for Thiocolchicoside, 0.043μg/ml and 0.132μg/ml for Dexketoprofen and for Method-2 were found to be 0.0093μg/ml and 0.028μg/ml for Thiocolchicoside, 0.055μg/ml and 0.168μg/ml for Dexketoprofen respectively. The developed methods were successfully applied to estimate the amount of Thiocolchicoside and Dexketoprofen in bulk and tablet dosage form.